Is it assessment of learning or assessment for learning? (South East Asia Journal of Public Health, 2015)
Assessment is a central feature of teaching and the curriculum. It powerfully frames how students learn and what students achieve. It is one of the most significant influences on students experience of higher education and all that they gain from it. The reason for an explicit focus on improving assessment practice is the huge impact it has on the quality of learning.1Students should realize that assessment can be an opportunity for learning, rather than just something to be endured and suffered.2'Institutions should ensure that appropriate feedback is provided to students on assessed work in a way that promotes learning and facilitates improvement'.3DOI: http://dx.doi.org/10.3329/seajph.v4i1.21847 South East Asia Journal of Public Health Vol.4(1) 2014: 72-74